Microplastics origins, risks, and mitigation - Singh, Baljinder; Upadhyay, Santosh Kumar (Elsevier, 2025)
Microplastics: Origins, Risks, and Mitigation discusses the sources, origin, and health risk assessment of microplastics in the environment. The various contamination indices, like contamination factor, atmospheric behavior, enrichment factor, and marine pollution are also included to provide further context on the state of microplastics in the environment and environmental impacts. The book present reviews on microplastics toxicology research, health hazards, and green remedial solutions for pollution control in terrestrial and aquatic environments, aiming to provide scientists and researchers with the knowledge to combat microplastic pollutants through sustainable means. Covering a variety of approaches, techniques, and scenarios, this book is a key resource for environmental scientists working to address microplastic environmental pollutants. It presents reviews on microplastics toxicology research, health hazards, and green remedial solutions for pollution control in terrestrial and aquatic environments